Sometimes Your Best Just Ain't Good Enough: The Worldwide Evidence on Well-Being Efficiency - Milena Nikolova; Olga Popova (Institute of Labor Economics (IZA), 2017)
Despite the burgeoning happiness economics literature, scholars have largely ignored explorations of how individuals or countries translate given resources into well-being. Using a balanced panel on 91 countries from Gallup Analytics between 2009–2014 and borrowing insights from production theory, we investigate whether nations in our sample efficiently convert their current resources (i.e. income, education and health) into subjective well-being. Our results imply that well-being efficiency gains are possible worldwide. We find that unemployment and involuntary part-time employment are associated with lower efficiency, while good institutions as proxied by the rule of law, as well as social support and freedom perceptions improve it. Within-country investigations for Bulgaria – an upper-middle-income country that often lurks at the bottom of the international well-being rankings – demonstrate that efficiency is lower among the unemployed, divorced/separated, widowed, the old, large households and those with children, while living in a city, freedom, generosity and social support improve efficiency. This paper provides the first evidence from an international panel concerning the issue of whether higher well-being levels are possible with current resources and raises policy-relevant questions about the appropriate instruments to improve well-being efficiency.
Keywords: D60; I31; O15; P52; 330; happiness; subjective well-being; efficiency analysis; conversion efficiency; comparative analysis